(Electronics and Photonics Division Award Address) Compound Semiconductors: A Retrospective. (25th October 2017) - Buckley, D. Noel
Abstract : The very first State-of-the Art Program on Compound Semiconductors (SOTAPOCS I) was called to order at the 166 th Meeting of The Electrochemical Society in New Orleans in the Fall of 1984. The first lightwave transmission system was then less than 4 years old and the first commercial cell phone was less than 3 years old. In fact, CW operation of a semiconductor laser at room temperature had been achieved less than 15 years before and even the transistor was still relatively young at 37 years. Our world has changed dramatically in the intervening years and compound semiconductors have played a vital role in the technologies that brought about that change. This paper looks back on some of the highlights and milestones in the development of compound semiconductors, and recalls some of the events along the way, and the key role played by The Electrochemical Society.